Assessing early literacy using school-based assessment / Nur Amalina Dayana Abd Aziz - Nur Amalina Dayana , Abd Aziz (2021)

(untitled)
Early literacy is an important foundation for learning. The importance of having mastered literacy early is not limited to students’ success at school but also extends into their after-school lives. Students with a good foundation in literacy are better prepared to participate as citizens. In line with the Ministry of Education Malaysia’s vision of producing world-class citizens, school-based assessment was first implemented in primary schools in 2011. Various studies on aspects such as teachers’ readiness, knowledge, understanding and practice of school-based assessment have been conducted using the quantitative method and within the context of secondary schools. The current study therefore aims to examine the assessment methods in the ESL (English as a second language) classroom at two national primary schools and to identify teachers’ perceptions of the use of school-based assessment in relation to the practice of early literacy assessment in the ESL classroom. The research design utilised is case study, with the qualitative approach used to collect data, comprising interviews, classroom observation, and relevant document collection. The data collected are then analysed using thematic analysis approach. The study reveals that teachers used various assessment practices including observation, questioning, giving tasks and providing feedback. These practices are not used independently but are incorporated as formative assessment. Teachers felt that their lack of pedagogical and content knowledge are among the biggest challenge that teachers face in carrying out the early literacy assessment in the ESL classroom. Time constraints due to their excessive workload also contribute to the challenges. The study also reveals that pressure from parents to hold examinations and lack of commitment from senior stakeholders in implementing the Ministry’s school-based assessment initiative contradicts with the purpose of having the assessment in the first place. This research infers that information is essential in ensuring quality teaching and assessment can take place in order to achieve the objectives at all level, which requires stakeholders such as the education agencies and parents to be empowered with training and input to be on the same page as teachers and be able to play their role in facilitating the assessment effectively. Further comparative research in various context concerning school-based assessment within the setting of primary school to broaden and deepen the literature are also recommended.